2006
DOI: 10.1007/s00246-005-0942-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin T and Cardiac Dysfunction in Extremely Low-Birth-Weight Infants

Abstract: Extremely low-birth-weight (ELBW) infants frequently manifest signs of cardiac dysfunction requiring inotropic support. It is not clear if this is due to cardiac injury, which can be monitored by measuring cardiac troponin T (cTnT). We performed a nested prospective cohort study at a university level III neonatal intensive care unit. The study included 27 infants weighing between 500 and 999 g. Exclusion criteria included evidence of sepsis, use of postnatal steroids, and cardiac anomalies. Measurements includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
3
7
0
2
Order By: Relevance
“…Moreover, cTnT was greatest in babies receiving dopamine with or without PDA. Similarly, Cruz et al also found highest levels of cTnT in babies requiring pressor support, and there was no relationship of cTnT with PDA, shortening fraction % or mVcfc in low birth weight babies (7). However, in our serial observations, multiple regression demonstrated CO inversely related to cTnT (Table2).…”
Section: Ctntsupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, cTnT was greatest in babies receiving dopamine with or without PDA. Similarly, Cruz et al also found highest levels of cTnT in babies requiring pressor support, and there was no relationship of cTnT with PDA, shortening fraction % or mVcfc in low birth weight babies (7). However, in our serial observations, multiple regression demonstrated CO inversely related to cTnT (Table2).…”
Section: Ctntsupporting
confidence: 71%
“…Despite prior studies [6,7], the information on sequential postnatal values of these markers in VLBWI and their hemodynamic implications is scant. In particular, no study has prospectively assessed the relationship of severity of illness [SNAPPE-II score [8][9][10][11][12], with sequential BNP, cTNT and related echocardiographic functional indices in VLBWIs during the first postnatal week.…”
Section: Introductionmentioning
confidence: 99%
“…Also, inotropic drugs were administered signifi cantly more frequently to asphyctic newborns (about two-fi fths of subjects) if compared to the control group (without such therapy). The main reason for administration of inotropes, as in other studies, was hypotension, which, if associated with hypovolemia and lactacidosis, increases oxygen consumption and further reduce cardiac contractility (7,9,23).…”
Section: Discussionmentioning
confidence: 92%
“…This parameter is often depressed after birth asphyxia and is a useful marker of severity and a prognostic indicator in asphyxia (16). In addition, troponin T, a marker of cardiac injury, was measured (1,17). To assess activation or suppression of mitochondrial apoptotic and survival pathways in myocardial left ventricular tissue, the protein level of apoptosis executioner cysteinyl aspartate-specific protease-3 (caspase-3) was determined.…”
Section: Articles Seehase Et Almentioning
confidence: 99%